Selliguea quinquefida (Polypodiaceae), a new calciphilous species from a karst area in Guangxi, China - Wei, Hong-Jin (Phytotaxa, 2024)
Selliguea quinquefida (Polypodiaceae), a new calciphilous species from Guangxi, China, is described and illustrated. The new species is the second within the genus with simple and palmate fronds and unique in having simple laminae with cordiform bases. It grows in a peculiar habitat with its rhizome creeping deeply within hardened chalky soils on limestone under relatively dry conditions and always bears palmately 5-lobed fronds with pentagonal shape when fully developed. The differences and habitats among S. quinquefida and all other species with palmate fronds in the genus are discussed.